KOLABORASI AKADEMIK DAN PEMBELAJARAN MAHASISWA DALAM DOKUMENTASI KEWIRAUSAHAAN BERBASIS BUDAYA DI RUMAH TENUN JO LA TERRE EKAFALO - Libertha Monemnasi; Elmagondulfa Habu Lelo; Yustina Oni Nona; Maria Stefani Elu (LPPM STP St. Petrus Keuskupan Atambua, 2025)
This community service activity aims to bridge students’ learning experiences with local culture-based entrepreneurship practices at Jo La Terre Ekafalo Weaving House, Timor Tengah Utara. Students conducted an internship to study production processes, traditional weaving techniques, and the management of culturally-based creative enterprises. Although the activity did not directly intervene in the partner’s operations, the presence of students and lecturers provided several positive impacts, including network enhancement, increased visibility of the partner, external validation, internal reflection on business processes, and additional documentation. This approach emphasizes participatory learning, respect for local practices, and the development of students’ reflective capacities. The activity is expected to serve as a model for academic collaboration that acknowledges partner achievements while providing meaningful learning experiences for students.